Rethinking the Emergence and the Practice of Three Praetorian States in Southeast Asia: A Comparative Study between Indonesia, Myanmar and Thailand - Muhammad Indrawan Jatmika (Institute of International Studies, 2020)
Military forces have had many important roles in political life in Southeast Asia where the military has a full power or major role and influence in the domestic politics. These forms of military intervention in domestic politics are called praetorianism, which is characterized by the military being more inclined to take care of domestic political affairs rather than carrying out its professional duties as guardians of sovereignty from external threats. We can find this practice from seeing the New Order regime in Indonesia to the Military Junta of Myanmar and Thailand. This paper aims to analyze what factors are the background of the widespread practice of praetorianism and how the practice can last for a certain period of time, even still to this day in Southeast Asia. The main argument is the weak political institutions and the low political culture of developing country are the main causes of various intervention efforts made by the armed forces in the domestic political realm of a country.